Kualitas Saus Tomat menggunakan metode Roasting - Haryopi Isnan; Lise Asnur (Student Scientific Creativity Journal, 2024)
This research was motivated by the absence of research on analyzing the quality of tomato sauce using the roasting method. The aim of this research is to determine the quality of tomato sauce using the roasting method regarding aroma, texture, color and taste. As well as knowing how to process tomato sauce using the roasting method, developing creativity in processed food products, adding information about processing tomato sauce, providing information to the public on how to process tomato sauce using the roasting method, increasing sales value, food security and product quality by empowering food ingredients. local. Producing tomato sauce with the best results can also be utilized and preserved by future generations. This type of research is a pure experiment, namely conducting direct experiments on the quality of tomato sauce using the roasting method. This experiment is also called a single factor experiment because it only analyzes the influence of one factor, namely the influence of the roasting method on the quality of tomato sauce. This research stage will be carried out using organoleptic testing, carried out by 3 panelists on the quality of tomato sauce which includes aroma, texture, taste and color. This research was carried out 3 times repeatedly by distributing questionnaires to 3 panelists. After determining the panelists. prepare tools and materials to carry out experiments to be carried out. After that, process the tomato sauce using the roasting method 3 times for the panelists.